No-reference video quality assessment by HEVC codec analysis - Xin Huang; Sogaard, Jacob; Forchhammer, Soren (2015 Visual Communications and Image Processing (VCIP), 2015)
This paper proposes a No-Reference (NR) Video Quality Assessment (VQA) method for videos subject to the distortion given by High Efficiency Video Coding (HEVC). The proposed assessment can be performed either as a Bitstream-Based (BB) method or as a Pixel-Based (PB). It extracts or estimates the transform coefficients, estimates the distortion, and assesses the video quality. The proposed scheme generates VQA features based on Intra coded frames, and then maps features using an Elastic Net to predict subjective video quality. A set of HEVC coded 4K UHD sequences are tested. Results show that the quality scores computed by the proposed method are highly correlated with the subjective assessment.